A missense variant Arg611Cys in LIPE which encodes hormone sensitive lipase decreases lipolysis and increases risk of type 2 diabetes in American Indians. Issue 3 (28th October 2021) - Muller, Yunhua L.; Sutherland, Jeff; Nair, Anup K.; Koroglu, Cigdem; Kobes, Sayuko; Knowler, William C.; Van Hout, Cristopher V.; ,; Shuldiner, Alan R.; Hanson, Robert L.; Bogardus, Clifton; Baier, Leslie J.
Abstract: Aims: Hormone sensitive lipase (HSL), encoded by the LIPE gene, is involved in lipolysis. Based on prior animal and human studies, LIPE was analysed as a candidate gene for the development of type 2 diabetes (T2D) in a community‐based sample of American Indians. Materials and methods: Whole‐exome sequence data from 6782 participants with longitudinal clinical measures were used to identify variation in LIPE . Results: Amongst the 16 missense variants identified, an Arg611Cys variant (rs34052647; Cys‐allele frequency = 0.087) significantly associated with T2D (OR [95% CI] = 1.38 [1.17–1.64], p = 0.0002, adjusted for age, sex, birth year, and the first five genetic principal components) and an earlier onset age of T2D (HR = 1.22 [1.09–1.36], p = 0.0005). This variant was further analysed for quantitative traits related to T2D. Amongst non‐diabetic American Indians, those with the T2D risk Cys‐allele had increased insulin levels during an oral glucose tolerance test (0.07 SD per Cys‐allele, p = 0.04) and a mixed meal test (0.08 log10 µU/ml per Cys‐allele, p = 0.003), and had increased lipid oxidation rates post‐absorptively and during insulin infusion (0.07 mg [kg estimated metabolic body size EMBS] −1 min −1 per Cys‐allele for both, p = 0.01 and 0.009, respectively), compared to individuals with the non‐risk Arg‐allele. In vitro functional studies showed that cells expressing the Cys‐allele had a 17.2% decrease in lipolysis under isoproterenol stimulation ( p = 0.03) and a 21.3% decrease in lipase enzyme activity measured by using p ‐nitrophenyl butyrate as a substrate ( p = 0.04) compared to the Arg‐allele. Conclusion: The Arg611Cys variant causes a modest impairment in lipolysis, thereby affecting glucose homoeostasis and risk of T2D.